Future Perspective for Radiation Dose Reduction techniques in Computed Tomography - A Study - Balasubramaniam, Vivekanadam (Journal of Innovative Image Processing, 2021)
The Computed Tomography (CT) image quality is determining by appropriate radiation dose in CT examination. Increases of the radiation dose become dangerous for our health such as induces of cancer, skin injuries, heritable mutations, reddening, burn the skins, etc. Therefore, the dose management study in the CT scanning procedure is one of the most important factors. This research article focuses on the use of the dose effectively in pediatric CT and cardiac CT scan procedures. Besides, the paper comprises dose hunt-down, auditing the scanner utilization, patient safety for the hospital association. This research article discusses radiation dose reduction techniques for effective dose in the view of future perspective in CT scan. This research article suggesting an appropriate technique to reduce the dose effectively in CT images during scanning. The effective dose test was conducted after reviews and ideas from future perspective designs.